2010
DOI: 10.1377/hlthaff.2009.0089
|View full text |Cite
|
Sign up to set email alerts
|

Racial And Ethnic Disparities In Dental Care For Publicly Insured Children

Abstract: Poor oral health has important implications for the healthy development of children. Children in Medicaid, especially Latinos and African Americans, experience high rates of tooth decay, yet they visit dentists less often than privately insured children. Even Latino and African American children with private insurance are less likely than white children to visit dentists and have longer intervals between dental visits. Furthermore, Latino and African American children in Medicaid are more likely than white chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 24 publications
1
30
2
1
Order By: Relevance
“…39,40 Minority children have more symptom-related dental visits than their peers 17 and have longer intervals between visits. 41 In some states, African American Medicaidenrolled children receiving dental care were less likely than their white peers to receive comprehensive dental services, including restorative and surgical treatment. 42 These same children were also more likely to be treated by dental providers who mostly provide diagnostic and preventive dental services.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Minority children have more symptom-related dental visits than their peers 17 and have longer intervals between visits. 41 In some states, African American Medicaidenrolled children receiving dental care were less likely than their white peers to receive comprehensive dental services, including restorative and surgical treatment. 42 These same children were also more likely to be treated by dental providers who mostly provide diagnostic and preventive dental services.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from Wisconsin, New Jersey, and Maryland demonstrates that Black Americans, especially those with no or public insurance and of low socioeconomic status, have higher rates of ED visits than whites (710). The most commonly cited reasons for these high rates include poor overall and oral health combined with a lack of access to dental insurance and care (79, 1113). However, little explanatory work has been done in this area.…”
Section: Introductionmentioning
confidence: 99%
“…2 As with medical care, numerous studies also have found that both disease burden and access to oral health care are associated with income, 3 race and ethnicity, 4 language, 5 and insurance status and type. 6 These factors are associated with barriers to access in underserved communities such as affordability, lack of provider availability, inadequate transportation, and low health literacy around the need for oral health care. Whereas nationally almost 60% of individuals with high incomes had a dental visit in the past year, less than 30% of low-income patients (those with incomes below 200% of the federal poverty level) had a dental visit in the past year.…”
mentioning
confidence: 99%